2015
DOI: 10.1115/1.4032019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flow Rates on Operation of a Solar Thermochemical Reactor for Splitting CO2 Via the Isothermal Ceria Redox Cycle

Abstract: A prototype 4 kW solar thermochemical reactor for the continuous splitting of carbon dioxide via the isothermal ceria redox cycle is demonstrated. These first tests of the new reactor showcase both the innovation of continuous on-sun fuel production in a single reactor and remarkably effective heat recovery of the sensible heat of the reactant and product gases. The impact of selection of gas flow rates is explored with respect to reactor fuel productivity and external energy costs of gas separation and pumpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…The authors reported thermal efficiencies up to 5.22%. More recently, Fosheim et al evaluated CLDRM in a solar cavity receiver integrated with highly effective gas‐phase heat recuperation; the reactor prototype consists of a concentric array of coaxial alumina tubes that each contain a packed bed of ceria and alumina reticulated porous ceramic. Here, ten isothermal chemical‐looping cycles were consecutively performed with 336 g of ceria, or 1/6th of the total reactor capacity, at two tube temperatures (i.e., 955 and 1000 °C) and the following gas flow rates: 5.5 μmolCH4 s −1 g −1 (diluted with 1.7 μmolN2 s −1 g −1 ) and 7.1 μmolCO2 s −1 g −1 for reduction and oxidation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported thermal efficiencies up to 5.22%. More recently, Fosheim et al evaluated CLDRM in a solar cavity receiver integrated with highly effective gas‐phase heat recuperation; the reactor prototype consists of a concentric array of coaxial alumina tubes that each contain a packed bed of ceria and alumina reticulated porous ceramic. Here, ten isothermal chemical‐looping cycles were consecutively performed with 336 g of ceria, or 1/6th of the total reactor capacity, at two tube temperatures (i.e., 955 and 1000 °C) and the following gas flow rates: 5.5 μmolCH4 s −1 g −1 (diluted with 1.7 μmolN2 s −1 g −1 ) and 7.1 μmolCO2 s −1 g −1 for reduction and oxidation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel is produced continuously by alternating the gas flows between reactive elements. The design gas flow rates and cycling period are set to maximize reactor thermal efficiency and fuel productivity (Hathaway et al, 2015;Venstrom et al, 2014). The design flow rates are 0.67 Â 10 À 4 mol s À 1 g ceria À 1 of N 2 and CO 2 for a 200 s cycle equally split between reduction and oxidation.…”
Section: Reactormentioning
confidence: 99%
“…The reactor is well insulated to reduce thermal losses to the ambient. Based on operation of the reactor, thermal losses are anticipated to equal 35% of the absorbed solar energy (Hathaway et al, 2015).…”
Section: Reactormentioning
confidence: 99%
See 2 more Smart Citations